Electronic literature as part of english literature - De Gregorio Robledo, Yolanda (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This essay introduces an approach to teach electronic literature in English Studies students; first introduces to the students what electronic literature is, that is, its main features, goals and genres. Secondly, it provides examples of women writers and their importance in the development of this kind of literature. Thirdly, it shows two electronic literary works written by women that may be part of the course’s core readings. This article dives into and breaks apart these literary texts through an introduction and a close reading of them.